MINAT ORANG TUA MEMASUKAN ANAK KE SMA ISLAM TERPADU - Muhammad Nur Agung Persada (Conciencia, 2018)
Education is a very important thing in human life. The progress of a nation depends on the education of the nation. This means that if the education of a nation can produce quality people physically and mentally, the nation will automatically progress, be peaceful and peaceful. This research is qualitative in nature with inductive thinking logic and the type is case studies, to obtain this data through interviews, observations, questionnaires and documentation. The sample of this study was 20 parents of students, this research activity is to describe intensively and in detail about the symptoms and social phenomena under study. Thus this study uses a descriptive analysis approach because the results of this research are descriptive data in the form of written or oral words and the results of research on parents of students who are the object of research to be observed as well as other matters relating to the problem under study. Data analysis is performed through three activities that occur simultaneously, namely data reduction, data presentation, drawing conclusions or verification. The results of this study indicate the main reason for parents interested in enrolling children in Izzuddin Integrated Islamic High School because of the application of the Islamic religious education system implemented by Izzuddin Integrated Islamic High School and there are also accompanying factors such as school modernization, easy access or because of the boarding. Expectations of parents of students sending their children to Izzuddin Integrated Islamic High School so that their children can understand religious teachings well not only theoretically but must be applicable.